(untitled) (Itinera, 2019)
The current museographical approach seems to go towards a form of interdisciplinarity, which leverages the encounter between visual and performing arts. From the Tate Gallery in London to the Palais de Tokyo in Paris, this dialogue not only gives rise to aesthetic experiences but also defines new forms of exhibitions: choreographed exhibitions. Within a migration from the black box to the white cube, the theatrical body becomes a work of art, through a process of objectivation. Likewise, the exhibition space turns into a hybrid place of creation. Through a kind of ontological negotiation between different art languages, the beholder is thus called into question: his participation is choreographed, as well as the very act of observation.